Fault-tolerant edge-pancyclicity of locally twisted cubes LTQn - Xu, Xirong; Zhang, Huifeng; Lingqi, Zhao; Zhang, Zhe; Yang, Yuansheng (Utilitas Mathematica, 2020)
The n-dimensional locally twisted cube LTQn is a variant of the hypercube, which possesses some properties superior to the hypercube. This paper investigates the fault-tolerant edge-pancyclicity of LTQn, and shows that if LTQn (n ≽ 5) contains at most n - 2 faulty vertices and/or edges then, for any fault-free edge e and any integer ℓ with 7 ≼ ℓ ≼ 2n — fv there is a fault-free cycle of length ℓ containing the edge e, where fv is the number of faulty vertices. The result is optimal in some senses. © 2020 Utilitas Mathematica Publishing Inc.. All rights reserved.